Pakistan’s first medicine price deregulation policy: assessing its impact on prices, affordability, and availability of oral anti-diabetic medicines in private pharmacies - Saeed, Amna; Shukar, Sundus; Yasin, Najwa Ali; Yang, Caijun; Jiang, Minghuan; Aziz, Muhammad Majid; Zahoor, Haris; Sunnan-Ud-Din, Muhammad; Fang, Yu; Babar, Zaheer-Ud-Din (Frontiers in Pharmacology, 2025)
IntroductionPakistan’s highest diabetes prevalence necessitates equitable access to anti-diabetic medicines. This study evaluated the access to Oral antidiabetics (OADs) and the effect of Pakistan’s recently launched price deregulation policy—applicable to medicines not included on the National Essential Medicines List (non-NEML)—on their prices and affordability by comparing NEML and non-NEML OADs.MethodsA WHO/HAI methodology-based survey in 30 private pharmacies across six regions gathered prices and availability data of 30 OADs, including the Lowest Price Generic (LPG), Highest Price Generic (HPG), and originator brand (OB). These selected OADs consisted of 11 products from NEML and 19 non-NEML products, comprising 17 single-active ingredient and 13 multi-active ingredient formulations. Published and surveyed retail prices of OADs (in Pakistani Rupees, PKR) before and after deregulation were compared, and the policy’s effect was determined by difference-in-differences (DiD) analysis. Affordability for the lowest-paid employee and medicine availability in percentages were calculated.ResultsThe DiD analysis revealed that the unit prices of OADs were significantly increased by PKR 15.08 (OB), PKR 5.89 (HPG), and PKR 2.81 (LPG) (p < 0.05) within just 6 months of the policy’s introduction. Medicines listed on the NEML remained consistently cheaper than non-NEML, with differences of −30.20 for OBs, −9.83 for HPGs, and −7.51 for LPGs in PKR (p < 0.001). As per DiD interaction terms (NEML enlistment status × deregulation), a greater increase in prices of non-NEML OBs was observed compared to NEML counterparts (PKR −10.85, p ≈ 0.05), while differences observed for LPGs (PKR 0.77, p = 0.73) and HPGs (PKR -0.20, p = 0.95) were insignificant. Prices of both single and multi-active ingredient formulations also increased significantly (p < 0.05). Although most OADs had fair availability from 47% to 97% after deregulation, seven out of 30 OADs remained unaffordable at both time points, and the overall affordability declined significantly post-deregulation (p < 0.05).ConclusionThe study revealed significant price escalations for most OADs, particularly those not enlisted on NEML, highlighting access challenges for diabetic patients and necessitating targeted policy reforms that address key market-related factors to ensure equitable access to OADs.